PERAN ZAKAT DALAM OPTIMASI PORTOFOLIO INVESTASI ASET (Studi Kasus pada Bank Syariah Indonesia periode 2012-2014) - Ummay Mashithoh (INVENTORY: JURNAL AKUNTANSI, 2017)
The basic concept of a portfolio is how to allocate a certain amount of funds to various types of investments that will produce optimal profits. This study aims to determine how the role of zakat in optimizing the asset investment portfolio. The research population is the Indonesian Islamic Bank registered at Bank Indonesia in the 2011-2015 period. Determination of samples in this study using a purposive sampling method. The results of the study state that the role of zakat has an optimal effect on Islamic investment. The advantage of investing in sharia with an optimum portfolio and incorporating the zakat element is far greater than the previous portfolio without adding the element of zakat to it. Keywords: portfolio, zakat, Islamic bank.